Improved Energy Technologies for Rural Cambodia - World Bank (Washington, DC, 2013)
More than 90 percent of total household energy used in rural Cambodia comes from wood and charcoal, which will continue to be the primary energy source for many more years, especially for poorer people. Faced with this reality, it is clear that simple and affordable solutions to the problems associated with burning wood and charcoal should be addressed. One obvious solution is the production and wide dissemination of more efficient stoves, which can cut fuel consumption in half. The new, improved cook stoves are based on traditional stove models, but both are more efficient due to three main improvements in design: 1) the space between the pot and the pot-rest is reduced, 2) the grate has smaller holes, and 3) the combustion chamber is smaller. The effect is better combustion with less heat loss, a more complete burning of wood, and also less smoke. There are two models of improved cook stoves: the Neang Kongrey stove and the New Lao stove. The Neang Kongrey is a simple ceramic cook stove that sells for about $1.25 and lasts for 1-2 years. The New Lao Stove has metal cladding and insulation that adds at least two years to the stove's lifetime and increases its cost to about $4.